Effecting structural development in the Malaysian Islamic banking sector using conventional banking models (IIUC Business Review, 2022)
To a notable extent, one of the main causes of renewed interest in Islamic Social Finance has been the academia’s disillusionment with the contemporary Islamic Banking and Finance (IBF) sector’s ability to break free of the conventional banking system. IBF has developed into a financial system that mirrors conventional financial practices and values, albeit with Shariah compliance. Using the Malaysian Islamic banking system as a basis, this paper makes use of extant literature and a systemic perspective to categorically identify the systemic reasons for IBF’s structural development, and further proposes a practical means for achieving pointed, systemic and inclusive (stakeholder-oriented) development that has been sought in IBF. Furthermore, its propositions are grounded in a tried and tested model of conventional banking. The implications of this research are as straightforward as they are significant; that by looking at IBF development theory from a more systemic and practical perspective, there are still means to develop IBF according to its original founding values.IIUC Business Review Vol. 7-8, Dec. 2018-19 pp. 89-106